Usage and satisfaction on Online-based motorcycle taxi services among Indonesian students - Wok, Saodah; Rahmawati, Nada (University College of Islam Melaka, 2017)
Jakarta has been dealing with traffic congestion since 1990. The conventional motorcycle taxi known as Ojek came to battle this issue. By 2011, Gojek and other online-based motorcycle taxi companies came into being; this system helps students to save time and money. The objectives of this study are: (1) to test the level of usage of online-based motorcycle taxi services (ON-MOTOTAXI) among students; (2) to determine factors influencing students‘ satisfaction in using ON-MOTOTAXI; (3) to analyze the mediating effect of attitude on perception towards students‘ satisfaction of ONMOTOTAXI. Uses and Gratifications Theory (Blumler and Katz, 1974) is used to test the study. This study uses quantitative research design, employing survey method and using self-administered questionnaire as the research instrument. A total of 340 respondents were collected among Indonesian students at IIUM, Kuala Lumpur and at UIN Syarif Hidayatullah, Jakarta. Results reveal that the highest three ON-MOTOTAXI company used by the students are Gojek, Grab and Uber. Perception moderately influences students‘ satisfaction. Attitude partially mediates students‘ perception towards satisfaction on ON-MOTOTAXI. Thus, Uses and Gratifications Theory holds true for the usage and satisfaction towards the services.